Komunikasi Komunitas Skinhead Sidoarjo dalam Proses Pengambilan Keputusan Kelompok - Uzlifatul Ulum; Kukuh Sinduwiatmo (Kanal: Jurnal Ilmu Komunikasi, 2016)
The purpose of this research to expose the communication process skinhead community in Sidoarjo. This group decision making was to achieve destination and develop a community of Sidoarjo to be skinhead better in solidarity between members. This research used descriptive research method and the type of research was qualitative in-depth interview with data analysis process through three phases namely data reduction, the presentation of the data, the withdrawal of the conclusion. The results of this study indicated that members of the community who always did the Sidoarjo skinhead activities with shared together-especially in decision making towards the group. In this community of skinhead Sidoarjo used horizontal communication. The community of skinhead Sidoarjo had no formal structure, they prefer to be considered all the members have the same social status. Decision making groups of skinhead Sidoarjo used deliberation. Although each group in the decision-making process of deliberation, but also ask for opinions from the more senior or elderly women in community skinhead Sidoarjo.